"I Hate to Pull a Bullet out of My Body": Crisis-Ridden Men and Postcolonial Identity in Wong Kar-Wai's Cinematic Hong Kong. Issue 3 (3rd April 2019) - Lei, Chin-pang
Abstract : Gender representation is often related to politics, and the notion of masculinity is an effect of culture. Using masculine genres such as gangster films and martial art films as his departure points, the acclaimed Hong Kong director Wong Kar-wai has re-created male characters, such as the lovelorn policemen in Chungking Express (1994), an assassin who is set up and killed by his female partner in Fallen Angels (1995), and a kungfu master whose life is helpless and miserable during wartime in The Grandmasters (2013). Wong's male protagonists are far from heroic, and even seen as feminized and infantilized. These crises-ridden men on one hand reflect Hong Kong's political predicament brought about by its problematic postcolonial situation, and on the other hand show Hong Kong's ambivalent culture with its resistance to the fixed national identity. These alternative male characters created by Wong are used actively to articulate Hong Kong identities with the culture of ambivalence in the postcolonial situation. Until recent years, these texts still respond to the changing political climate and the ongoing anxiety in Hong Kong.